The impact of China on the South African manufacturing industry : implications of Chinese import penetration - Gupta, Varun (My University, 2016)
The global competitiveness of the South African manufacturing industry has declined over the last five years. Cheap imports mainly from China are displacing the local market for manufacturing, leading to a loss of jobs and the contraction of the domestic manufacturing industry. This is mainly caused by ineffective restrictions of importations and an unfavourable local manufacturing environment. As a result, the manufacturing industry in South Africa is contracting and contributing less to the national GDP, leading to a reduction in annual growth. To improve the situation, the government and main stakeholders in the South African manufacturing industry need to take comprehensive measures that will boost the local manufacturing industry, while at the same time maintaining a mutual and bilateral partnership with trade partners, such as China.
MBA
Keywords: Manufacturing industries -- South Africa. China -- Foreign economic relations -- South Africa.South Africa -- Foreign economic relations -- China.